HPV/E7 induces chemotherapy‐mediated tumor suppression by ceramide‐dependent mitophagy - Raquela J Thomas; Natalia Oleinik; Shanmugam Panneer Selvam; Silvia G Vaena; Mohammed Dany; Rose N Nganga; Ryan Depalma; Kyla D Baron; Jisun Kim; Zdzislaw M Szulc; Besim Ogretmen (EMBO Molecular Medicine)
Abstract Human papillomavirus (HPV) infection is linked to improved survival in response to chemo‐radiotherapy for patients with oropharynx head and neck squamous cell carcinoma (HNSCC). However, mechanisms involved in increased HNSCC cell death by HPV signaling in response to therapy are largely unknown. Here, using molecular, pharmacologic and genetic tools, we show that HPV early protein 7 (E7) enhances ceramide‐mediated lethal mitophagy in response to chemotherapy‐induced cellular stress in HPV‐positive HNSCC cells by selectively targeting retinoblastoma protein (RB). Inhibition of RB by HPV‐E7 relieves E2F5, which then associates with DRP1, providing a scaffolding platform for Drp1 activation and mitochondrial translocation, leading to mitochondrial fission and increased lethal mitophagy. Ectopic expression of a constitutively active mutant RB, which is not inhibited by HPV‐E7, attenuated ceramide‐dependent mitophagy and cell death in HPV(+) HNSCC cells. Moreover, mutation of E2F5 to prevent Drp1 activation inhibited mitophagy in HPV(+) cells. Activation of Drp1 with E2F5‐mimetic peptide for inducing Drp1 mitochondrial localization enhanced ceramide‐mediated mitophagy and led to tumor suppression in HPV‐negative HNSCC‐derived xenograft tumors in response to cisplatin in SCID mice.